Increased expression of c-myc proto-oncogene in biopsies of ulcerative colitis and Crohn's colitis. Issue 5 (May 1992) - Macpherson, A J; Chester, K A; Robson, L; Bjarnason, I; Malcolm, A D; Peters, T J
Abstract : The steady state levels of c-myc mRNA have been measured in RNA samples extracted from colonoscopic biopsies of inflammatory bowel disease patients obtained at routine endoscopy sessions. Biopsies were immediately frozen in liquid nitrogen limiting the ischaemic time to less than 15 seconds, and can be stored for up to 96 hours before separation of RNA. Yields of RNA using biopsies were 0.137 (0.041)% wet wt (mean (SD), n = 68), these are significantly better than those obtained from surgical material (0.064 (0.063)% wet wt (mean (SD), n = 21) where the tissue ischaemic time was 45 minutes to one hour 40 minutes. Functional activity of RNA extracted was demonstrated by the ability to direct in vitro protein translation in the rabbit reticulocyte system. We have used this technique to show that there is an increased ratio of steady state c-myc proto-oncogene expression in inflamed tissue from 18 patients with left sided ulcerative colitis and five patients with segmental Crohn's colitis, compared with an uninvolved region of the colon in each case. No difference in c-myc expression was seen in biopsies at least 30 cm apart in 11 control patients with no macroscopic or histological abnormalities. Increased expression of c-myc in inflammatory bowel disease is consistent with the activation of this proto-oncogene during altered cell cycle control resulting from the inflammatory process.